A Laboratory Evaluation of Contextual Factors Affecting Ratings of Speech in Noise: Implications for Ecological Momentary Assessment. Issue 4 (July 2019) - Jenstad, Lorienne M.; Gillen, Lise; Singh, Gurjit; DeLongis, Anita; Pang, Flora
Abstract : Objectives: As hearing aid outcome measures move from retrospective to momentary assessments, it is important to understand how contextual factors influence subjective ratings. Under laboratory-controlled conditions, we examined whether subjective ratings changed as a function of acoustics, response timing, and task variables. Design: Eighteen adults (age 21 to 85 years; M = 51.4) with sensorineural hearing loss were fitted with hearing aids. Sentences in noise were presented at 3 overall levels (50, 65, and 80 dB SPL) and 3 signal to noise ratios (0, +5, and +10 dB signal to noise ratio [SNR]). Listeners rated three sound quality dimensions (intelligibility, noisiness, and loudness) under four experimental conditions that manipulated timing and task focus. Results: The quality ratings changed as the acoustics changed: intelligibility ratings increased with input level ( p < 0.05); noisiness ratings increased at poorer SNRs ( p < 0.05); and loudness ratings increased as input level increased ( p < 0.05). Timing of rating was significant at the highest presentation level (80 dB SPL): Participants gave higher noise ratings while listening to the signal than afterward ( p < 0.05). Presence of a secondary task had no significant effect on ratings ( p > 0.1). Conclusions: The findings of this laboratory study provide evidence to support the conclusion that group-mean listener ratings of loudness, noisiness, and intelligibility change in predictable ways as level and SNR of the speech in noise stimulus are altered. They also provide weak evidence to support the conclusion that timing of the ratings (during or immediately after sound exposure) can affect noisiness ratings under certain conditions, but no evidence to support the conclusion that timing affects other quality ratings. There is also no evidence to support the conclusion that quality ratings are influenced by the presence of, or focus on, a secondary nonauditory task of the type used here. Abstract : Supplemental Digital Content is available in the text.